1993
DOI: 10.1128/jb.175.11.3661-3663.1993
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the modified folates in the extremely thermophilic archaebacterium Thermococcus litoralis

Abstract: The chemical structures of the two modified folates present in Thermococcus litoralis were established. These compounds, each containing a core structure of 1-[4-[[1-(2-amino-7-methyl-4-oxo-6-pteridinyl)-ethyllaminolphenyl]-1-deoxy-[1-c-D-ribofuranosylJ-ribitol, were characterized. The five position of the ribose in this core structure was ,8-linked to the C-1 of a poly-13(1--.4)N-acetylglucosamine having a chain length of four or five N-acetylglucosamine residues. Thus, these compounds are N-acetylglucosamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Hence, since UDP NAGs are the major, activated intermediates involved in the biosynthesis of both S-layers (22) and external structures, it may not be surprising that these compounds accumulate to such high intracellular concentrations in P. furiosus. In addition, both P. furiosus (44) and T. litoralis (43) have been shown to contain modified folates which have GlcNAc side chains attached. The reason for this is not known, but from a study (42) of methanopterin biosynthesis, it was concluded that GlcNAc residues are incorporated after folate synthesis.…”
Section: Vol 179 1997 Udp Amino Sugars In P Furiosus 1509mentioning
confidence: 99%
“…Hence, since UDP NAGs are the major, activated intermediates involved in the biosynthesis of both S-layers (22) and external structures, it may not be surprising that these compounds accumulate to such high intracellular concentrations in P. furiosus. In addition, both P. furiosus (44) and T. litoralis (43) have been shown to contain modified folates which have GlcNAc side chains attached. The reason for this is not known, but from a study (42) of methanopterin biosynthesis, it was concluded that GlcNAc residues are incorporated after folate synthesis.…”
Section: Vol 179 1997 Udp Amino Sugars In P Furiosus 1509mentioning
confidence: 99%
“…In the case of coenzyme M, (S)-sulfolactate, formed from phosphoenolpyruvate (PEP) and bisulfite, is an intermediate in the biosynthesis (28-30). In the case of methanopterin (24, 25) and several related modified folates (33,34,36), (S)-hydroxyglutaric acid (23) is incorporated into the coenzyme during its biosynthesis (32, 35). For coenzyme F 420 (6) and its ␥-polyglutamate derivatives (7, 8, 18), (S)-hydroxypropionic acid (S-lactic acid) becomes a part of the final structure.…”
mentioning
confidence: 99%
“…SHMT has been purified from both procaryotic and eucaryotic cells, and the cDNA sequences for more than 20 different forms are present in the SwissProt database. However, only limited information on SHMT from a member of the Archaea is available, in part because these organisms use modified folates as a coenzyme (13). These modified folates are not commercially available, making it difficult to assay for folate-requiring enzymes.…”
mentioning
confidence: 99%
“…The methanogens use methanopterin, a dimethylated pteridine (methyl groups at C-7 and C-9) connected to 1-(4-aminophenyl)-1-deoxy-D-ribitol (APDR), a common structural element found in all the currently known modified folates ( Fig. 1) (13,14). The hyperthermophile Sulfolobus solfataricus contains a modified folate which has structural features between those of the methanogenic modified folates and folate.…”
mentioning
confidence: 99%